نماذج التنبؤ بوضعية المركز المالي للمؤسسة الإقتصادية " دراسة حالة شركة النسيج للمواد الثقيلة MANTAL " - طويطي, مصطفى (جامعة مسيلة, 2018)
This article is intended to open the way for financial analysts in economic institutions to identify the most important ideas and new technologies that deal with the identification and analysis of the financial situation of the institution in order to detect early on the possibility of the occurrence of the events of unwanted and are taking the necessary measures to avoid the occurrence or minimize them . The study Beaver in 1966, the first attempt in the formulation of a mathematical model capable of determining the status of institution also followed by many of the studies carried out by other researchers , such as Altman , Sprinate and others . In order to stand on the importance of these models and their applications , relying on the applied study of one of the Algerian institutions and is a fabric material heavy MANTAL the state of Tlemcen .And has indicated as a result of the application of this model to the institution under study that the probability of exposure to the risk of bankruptcy is estimated at 73.8 % , which means they are in a critical financial position limit the possibility of survival and continuity in the exercise of activity and this is what requires the institution decision makers to move quickly and effectively in order to contain this danger and remedied according to the possibilities available
Keywords: financial diagnosis, prediction models, the financial position , Beaver , Altman , Z-Score